Bantuan Hukum Pro Bono sebagai Respon Sosial terhadap Ketimpangan Akses Keadilan di Indonesia - Mieke Malindo (Jurnal Hukum Lex Generalis, 2025)
Inequality in the access to justice concept is a fundamental issue in the  Indonesian legal system, especially for poor and vulnerable groups who are unable to access commercial legal services. Pro bono legal aid plays a strategic role as a form of social responsibility for lawyers in responding to this inequality. This article examines the contribution of pro bono legal aid in expanding access to social justice through a legal-normative approach and qualitative analysis of regulations, professional codes of ethics, and practices in the field. The results of the study show that although there is a normative obligation for lawyers to provide pro bono services, its implementation still faces various obstacles, such as a lack of institutional support, low appreciation and incentives, and operational constraints. This situation highlights the need to strengthen policies, budgets, and synergies among stakeholders, including the state, professional organizations, legal aid institutions, and educational institutions. On the other hand, there is also a need to strengthen the monitoring and evaluation system for overseeing pro bono obligations as part of monitoring and documenting achievements or obstacles faced, as part of evaluating and developing pro bono policies in the future. It is hoped that pro bono legal aid will become an effective instrument in building a fair, progressive, and more inclusive judicial system in the future.